Relationship between Alcohol Consumption and Metabolic Syndrome according to Facial Flushing in Korean Males - Kim, Min-Yeong (The Korean Academy of Family Medicine, 2012)
BACKGROUND: The aim of the present study is to evaluate the risk of metabolic syndrome (MS) according to alcohol consumption for those subjects showing facial flushing, as well as the absence of facial flushing. METHODS: One thousand two hundred and one males were recruited in the health promotion center of a university hospital. Evaluation of alcohol consumption and facial flushing was assessed via questionnaires and interviews. The criteria for MS were defined according to the National Cholesterol Education Program Adult Treatment Panel III criteria with a modified waist circumference cutoff value (men ≥ 90 cm) for Korean subjects. Subjects were divided into three groups according to the amount of alcohol they consume: nondrinkers, moderate drinkers (≤14 standard drinks per week), and heavy drinkers (>14 standard drinks per week). They were also separated into two groups according to facial flushing: non-flushers (no occurrence) and flushers (steady occurrence). Factors related to MS were assessed by logistic regression analysis. RESULTS: In non-flushing moderate drinkers, the risk of MS did not significantly increase compared to non-drinkers. However in flushing moderate drinkers, there was significant increase (odds ratio [OR], 1.81; confidence interval [CI], 1.08 to 3.06) compared to non-drinkers. In non-flushing and flushing heavy drinkers, significant increase (OR, 2.23; CI, 1.23 to 4.04; OR, 2.90; CI, 1.25 to 6.73, respectively) was evident compared to non-drinkers. CONCLUSION: Non-flushing moderate drinkers did not show an increased risk of metabolic syndrome compared to the non-drinkers, but flushing moderate drinkers showed an increased risk of metabolic syndrome compared to non-drinkers.